Impact of value chain activities on value addition in paddy farming in Nepal - Khanal, Kapil (Management Dynamics, 2020)
Objective: The objective of this research is to measure the impact of processing activities on value addition in paddy farming in Bagmati zone. Methods and Materials: For the efficient completion of the research, samples of 400 farmers were taken from four districts of Bagmati Zone: Kathmandu, Bhaktapur, Lalitpur and Kavrepalanchowk respectively. Simple random sampling method was used where every element of the study population had equal and non zero chance of being selected as a sample of the study. The research study is completed using a blend of descriptive and causal research design. Quantitative method is used in the research where the questionnaires are close ended with fixed options. Results and Conclusion: It is found that there was positive significant relationship between the method of farming, storing and hulling on value addition in paddy whereas there was no significant relationship between the harvesting and value addition in paddy.